Internal diseases propedeutics: textbook for foreign students of Medical Higher Educational InstitutionsInternal Diseases Propedeutics: textbook for foreign students of Medical Higher Educational Institutions - Ивашкин, В. Т. терапия, гастроэнтерология 19390324 Владимир Трофимович (GEOTAR-Media, 2016)
As a foundation to a successful career in clinical medicine every physician needs to be able to establish a good rapport with the patient, accurately record all presenting symptoms and signs, and finally make an accurate diagnosis. "Internal diseases propedeutics" offers a thorough grounding in the principles of the physical examination and provides a detailed account of the symptoms and signs of diseases affecting the body systems. This textbook includes chapters on diagnosis of pulmonary, cardiovascular, digestive, genitourinary, nutritional, endocrine disorders and diseases ofblood. The book covers both basic clinical skills, and high technology investigations and interventions that are utilised today by the physician. The "Internal diseases propedeutics" ensures that it will remain an invaluable source of information for all medical students and junior doctors of all specialities in their early years of clinical practice. Рекомендовано УМО по медицинскому и фармацевтическому образованию вузов России в качестве учебного пособия для студентов медицинских вузов, обучающихся на английском языке